THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND COMPANY SIZE ON CAPITAL STRUCTURE: EVIDENCE FROM INDONESIA FOOD AND BEVERAGE COMPANIES - Angela, Karin Novena; Ekadjaja, Agustin (Graduate Program of Universitas Tarumanagara, 2025)
In the era of globalization, the business world is experiencing rapid development which triggers intense competition between companies, so that systematic and planned financial management is needed in order to survive. Capital structure holds a significant position in ensuring financial stability and operational sustainability for a business, where the right funding policy can increase profits and investor confidence. Effective management of funds, ncompassing both internal and external sources, enables businesses to optimize prospects within a highly competitive market landscape. The purpose of this study was to determine the effect of profitability, liquidity, and company size on entities in the food and beverage subsector companies listed on the Indonesia Stock Exchange during the period 2021-2023. This study used purposive sampling approach, resulting in 96 data on food and beverage subsector companies listed on the IDX during the period 2021-2023. Data analysis wa performed using Eviews 12 software. The hypothesis testing method in this research uses multiple linear regression models. The model estimation chosen is the Fixed Effect Model to ensure the suitability of the multiple linear regression model in the data analysis used. This study measures capital structure by employing the DER as the main parameter. The result obtained from this research shows that profitability has no significantly negatively effect on capital structure. Liquidity has a significantly negatively effect on capital structure. Company size has a significant positively effect on capital structure.